Disagreement Between Theoretical and Actual Phorcides Outcomes: Is Phorcides Inferior to Treating on the Manifest Refraction? [Letter] - Wallerstein A; Gauvin M (Clinical Ophthalmology, 2020)
Avi Wallerstein,1,2,* Mathieu Gauvin1,2,* 1Department of Ophthalmology and Visual Sciences, McGill University, Montreal, QC, Canada; 2Department of Research & Development, LASIK MD, Montreal, QC, Canada*These authors contributed equally to this workCorrespondence: Avi WallersteinMD Level, 1250 Rene-Levesque Blvd W, Montreal, QC H3B 4W8, CanadaTel +1 514-908-9888 Ext 2273Email awallerstein@lasikmd.com We read with interest “Topography-Guided Refractive Astigmatism Outcomes: Predictions Comparing Three Different Programming Methods.”1 In the Manifest group, the calculated theoretical outcomes revealed an unexpectedly elevated postoperative refractive astigmatism average error of 0.56 ± 0.22 D.1 This large amount of theoretical postoperative cylinder was not replicated in a recent real-world clinical study by the same authors, comparing actual topography-guided LASIK outcomes in Phorcides versus manifest-treated eyes.2 The reported empirical postoperative astigmatism error average in the Manifest group was as  low as 0.15 D, fourfold better than that reported in the current theoretical outcomes study.1   View the original paper by Stulting and colleagues